2017
DOI: 10.1371/journal.pone.0175458
|View full text |Cite
|
Sign up to set email alerts
|

Human exploitation assisting a threatened species? The case of muttonbirders and Buller’s albatross

Abstract: Albatrosses are flexible and adaptable predators, relying on live prey as well as carrion. Use of predictable food sources and reliance on human-produced resources are well-known trait in long-range feeders like albatrosses and petrels. Breeding Buller’s albatrosses studied at Solander I. (Hautere), New Zealand fed their chicks the remains of sooty shearwater juveniles (tītī in Māori), which are harvested from nearby muttonbirding sites. Evidence of this food type was found at over 10% of nests examined, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…in stomachs suggested that WHDPs feed at the edge of the continental shelf (Imber & Nilsson 1980). WHDPs share these seas with a suite of seabird species including Sooty Shearwaters (Puffinus griseus; Shaffer et al 2006), Cook's Petrels (Pterodroma cookii; Rayner et al 2008a), Buller's Albatrosses (T. bulleri; Waugh et al 2017), and Whiteheaded Petrels (P. lessonii; Taylor et al 2020).…”
Section: Whdp Movements and Distributionmentioning
confidence: 99%
“…in stomachs suggested that WHDPs feed at the edge of the continental shelf (Imber & Nilsson 1980). WHDPs share these seas with a suite of seabird species including Sooty Shearwaters (Puffinus griseus; Shaffer et al 2006), Cook's Petrels (Pterodroma cookii; Rayner et al 2008a), Buller's Albatrosses (T. bulleri; Waugh et al 2017), and Whiteheaded Petrels (P. lessonii; Taylor et al 2020).…”
Section: Whdp Movements and Distributionmentioning
confidence: 99%
“…in stomachs suggested that WHDPs feed at the edge of the continental shelf (Imber & Nilsson 1980). WHDPs share these seas with a suite of seabird species including Sooty Shearwaters (Puffinus griseus; Shaffer et al 2006), Cook's Petrels (Pterodroma cookii; Rayner et al 2008a), Buller's Albatrosses (T. bulleri; Waugh et al 2017), and Whiteheaded Petrels (P. lessonii; Taylor et al 2020).…”
Section: Whdp Movements and Distributionmentioning
confidence: 99%